(untitled) (Laisvalaikio tyrimai, 2025)
Background. Emotional wellbeing and physical activity are key components of children’s health, learning, and social functioning. Schools provide a unique setting to support both domains, yet less is known about how school type and sex are related to emotional wellbeing and physical activity in younger school-age children. Objective. To examine the associations between emotional wellbeing and physical activity among primary school children and to assess differences according to sex and school type. Methods. A cross-sectional study was conducted in November 2024, which included 166 children in grades 1–4 from one rural, one urban, and one private school. Emotional state was assessed using the SAN scale, yielding scores for wellbeing and mood. Physical activity was measured using a self-report questionnaire, capturing weekly activity levels. Non-parametric tests (Mann–Whitney U) were used to compare groups, and Spearman’s correlation coefficients were calculated to examine associations between variables. Results. Wellbeing and mood were strongly and positively correlated (r = 0.70, p < 0.001), indicating a coherent construct of emotional wellbeing in this age group. No statistically significant differences in emotional wellbeing or physical activity were found between boys and girls (p > 0.05). Children attending private schools reported significantly lower wellbeing and mood scores compared with their peers in rural and urban schools (p < 0.001). Rural school children demonstrated higher physical activity levels than their peers in both urban and private schools (p ≤ 0.001). Physical activity was not significantly associated with either wellbeing or mood (p > 0.05). Conclusions. Emotional wellbeing among primary school children is closely interconnected, but it is more strongly related to school type than to sex or self-reported physical activity levels. School environment appears to play a meaningful role in shaping both emotional state and activity levels, highlighting the importance of supportive, health-promoting school settings in early education. Keywords: primary school children; physical activity; mood; emotional wellbeing